Flora das cangas da Serra dos Carajás, Pará, Brasil: Marantaceae - Saka, Mariana Naomi [UNESP] (FapUNIFESP (SciELO), 2017)
This taxonomic survey comprises the species of Marantaceae registered for the cangas of Serra dos Carajás, Pará, Brazil. Two species inhabit the cangas: Maranta ruiziana and Monotagma plurispicatum. Morphological descriptions of genera and species, illustrations, and additional remarks are also presented.
Flora of the cangas of Serra dos Carajás, Pará, Brazil: Marantaceae
Keywords: Cangas; FLONA Carajás; Flora; Marantaceae